Peran Kepala Sekolah untuk Menumbuhkan Gerakan Literasi Sekolah (GLS) di Mi Falahussyabab - Khasbi Ainun Najib (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to determine the role of the Principal's Leadership in growing the School Literacy Movement (GLS) at the level of Madrasah Ibtidaiyyah Falahussyabab Yogyakarta. . This research is a type of descriptive qualitative research with data collection techniques in the form of observation, interviews and documentation. The subjects in this study were the principal and class teacher. This research was conducted at MI Falahussyabab. The results of this study indicate that the Principal's Leadership Role at MI Falahussyabab in carrying out literacy programs are: (1) socializing literacy policy issues through open meetings by all classroom teachers and subject teachers; (2) create an organizational structure for the Literacy Team; (3) provide a reading corner in each class respectively. (4) school principals always remind teachers of school literacy programs; (5) providing library facilities for students to read; (6) familiarize students to read every day for 15 minutes before the learning process begins.